The Effects of NaI, KBr, and KI Salts on the Vapor-Liquid Equilibrium of the H2O+CH3OH System - Xu, Xianzhen; Zhang, Na; Zhou, Yu; Wang, Yan; Wang, Zonghua (Frontiers in Chemistry, 2020)
Vapor–liquid equilibrium (VLE) in chemical engineering are indispensable for the design of equilibrium separation processes such as distillation, absorption, extraction, and crystallization. VLE data were measured for H2O+CH3OH+NaI, H2O+CH3OH+KBr, and H2O+CH3OH+KI systems. By analyzing and summarizing the results of H2O+Methanol+Alkali metal halide systems, the salt effect of NaI, KBr and KI on vapor–liquid equilibrium were obtained. Simultaneously, a model based on the NRTL equation (non-random two liquid) was proposed to correlate and calculate the VLE for the systems. In addition, the assumption of solvation based on the hydration was introduced in this model. The proposed model can be successfully used to calculate the VLE for H2O+Methanol+Alkali metal halide systems.